Psychosocial risk factors for eating disorders. Issue 5 (9th May 2013) - Keel, Pamela K.; Forney, K. Jean
Abstract Objective: One goal in identifying psychosocial risk factors is to discover opportunities for intervention. The purpose of this review is to examine psychosocial risk factors for disordered eating, placing research findings in the larger context of how etiological models for eating disorders can be transformed into models for intervention. Method: A qualitative literature review was conducted focusing on psychological and social factors that increase the risk for developing eating disorders, with an emphasis on well‐replicated findings from prospective longitudinal studies. Results: Epidemiological, cross‐cultural, and longitudinal studies underscore the importance of the idealization of thinness and resulting weight concerns as psychosocial risk factors for eating disorders. Personality factors such as negative emotionality and perfectionism contribute to the development of eating disorders but may do so indirectly by increasing susceptibility to internalize the thin ideal or by influencing selection of peer environment. During adolescence, peers represent self‐selected environments that influence risk. Discussion: Peer context may represent a key opportunity for intervention, as peer groups represent the nexus in which individual differences in psychological risk factors shape the social environment and social environment shapes psychological risk factors. Thus, peer‐based interventions that challenge internalization of the thin ideal can protect against the development of eating pathology. © 2013 by Wiley Periodicals, Inc. (Int J Eat Disord 2013; 46:433–439)